Advanced nanocomposite materials for protective fencing suits: Enhancing biomechanical performance and sustainability - Alardah, A. H. S.; kuna, M.; Al-Ani, M.; Sliem, M. H. R.; Al-Qahtani, N. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
Fencing requires proper protective attire that ensures safety and allows for unrestricted movement by balancing flexibility, durability, and puncture resistance. This study investigates the potential of electrospun nanofiber composites, composed of polyacrylonitrile (PAN) and enhanced with reduced graphene oxide (rGO), as a sustainable alternative to traditional fencing suit materials. Characterization techniques such as scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and dielectric spectroscopy confirmed the uniform incorporation of rGO within the porous nanofiber structure, which enhances the distribution of mechanical loads and energy absorption. The dielectric characteristics of the composite suggest its suitability for applications in adaptive stiffness and motion sensing, thereby supporting advanced biomechanical functionalities. A key objective of this research is to support the production of Qatar`s first locally manufactured fencing suit, reducing import dependency and aligning with Qatar`s National Vision 2030 for sustainability and technological progress. Future research will focus on refining fiber alignment and conducting extensive mechanical testing to meet international standards for protective sportswear. This study advances the development of multifunctional sustainable textiles aimed at high-performance athletic protection.